Modeling store brand choice: Minimal effects of households' demographic features. (December 2015) - Cotes-Torres, Alejandro; Muñoz-Gallego, Pablo A.; González-Benito, Óscar
Highlights: We study main demographic factors that could affect store brand choice. We study 13 food categories in 2011 households over the course of two years. Household's economic status, household size and head of household's age affected this choice. Abstract: Demographic characteristics are factors that both managers and business consultants use to explain consumer behavior. However, their usefulness has been questioned by some researchers; this study considers their effect on store brand choice. The authors analyze purchases in 13 food categories by 2011 households over the course of two years using a binomial logit mixed model. The results reveal that the household's social class, household size, and the head of household's age affect this choice. A weak relationship emerges between the demographic variables and store brand choice though, indicating that for many years, retailers and business managers have been allocating vast financial resources to obtain data about demographic variables that barely affect real consumer behavior. The results also confirm prior research that indicates retailers should not segment by households' demographic features but rather should offer store brands and target all buyers with them similarly.